2008
DOI: 10.1007/s10548-008-0044-7
|View full text |Cite
|
Sign up to set email alerts
|

Neuromagnetic Activity During Recognition of Emotional Pictures

Abstract: Recently studied 'old' stimuli lead to larger frontal and parietal ERP responses than 'new' stimuli. The present experiment investigated the neuromagnetic correlates (MEG) of this 'old-new' effect and its modulation by emotional stimulus content. Highly arousing pleasant, highly arousing unpleasant and un-arousing neutral photographs were presented to the participants with the instruction to memorize them. They were later re-presented together with new photographs in an old-new decision task. In line with prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 53 publications
(82 reference statements)
3
4
1
Order By: Relevance
“…Furthermore, in a valence by sex interaction, women showed better accuracy for high valence pictures, an effect absent in men. These results corroborate previous findings of better accuracy for pleasant images (not controlling for arousal or sex) (Kissler and Hauswald, 2008;Lang et al, 1990b;Smith et al, 2004). Moreover, in the arousal by sex interaction, women showed less accuracy for high arousal stimuli, an effect absent in men.…”
Section: Accuracy and Reaction Timessupporting
confidence: 90%
See 2 more Smart Citations
“…Furthermore, in a valence by sex interaction, women showed better accuracy for high valence pictures, an effect absent in men. These results corroborate previous findings of better accuracy for pleasant images (not controlling for arousal or sex) (Kissler and Hauswald, 2008;Lang et al, 1990b;Smith et al, 2004). Moreover, in the arousal by sex interaction, women showed less accuracy for high arousal stimuli, an effect absent in men.…”
Section: Accuracy and Reaction Timessupporting
confidence: 90%
“…Bradley et al (1992) also found a delayed new RT for low valence/unpleasant images in a mixed sample. Unpleasant stimuli have been found to delay reaction times in several studies (Kissler and Hauswald, 2008;Maratos et al, 2001;Smith et al, 2004;Van Strien et al, 2009). Indeed, our group of men demonstrated an old-new effect 36% greater in response to unpleasant than to pleasant images.…”
Section: Accuracy and Reaction Timessupporting
confidence: 54%
See 1 more Smart Citation
“…On the neural level, positive content modulates recognition memory mostly via the familiarity-based frontal old/new effect (e.g. Kissler and Hauswald 2008;Schaefer et al 2011) for which we did not find significant effects.…”
Section: Discussioncontrasting
confidence: 79%
“…Elucidating the mechanisms of this advantage for pleasant stimuli is beyond the scope of the present study. Nevertheless, it has been theoretically suggested and empirically demonstrated repeatedly that healthy subjects hold profound biases towards pleasant in contrast to unpleasant and neutral stimuli (e.g., Deldin et al, 2001;Ferré, 2003;Herbert et al, 2008Herbert et al, , 2009Kiefer et al, 2007;Kissler and Hauswald, 2008;Koenig and Mecklinger, 2008;Monnier and Syssau, 2008;Schapkin et al, 2000;Watson et al, 2007). Thus, a processing bias in favour of pleasant stimuli may, at least during deep processing conditions, bias participants' evaluations and bodily emotional responses towards words with pleasant content.…”
Section: Discussionmentioning
confidence: 99%